Utilization of corn cob as a low cost biosorbent for the remediation of carbofuran - Yahya, Ezra Athira (Universiti Sains Malaysia, 2014)
The potential of corn cob as a natural low-cost biosorbent for the removal of carbofuran from the aqueous solution has been investigated. The effects of modification agents, modification ratio, adsorbent dosage, initial concentration and contact time, pH and temperature on the adsorption process were carried out. Sodium carbonate was identified as the best modification agent, with the adsorption uptake for carbofuran of 142.0 mg/g respectively. Modification ratio (MR) of 1.5 was identified as the best MR. The optimum adsorptive uptake and adsorptive removal of carbofuran are denoted at 148.82 mg/g and 74.77%, respectively at the adsorbent dosage of 0.3 g increasing the initial concentration of showed an increase of adsorption uptake and removal efficiency with prolonging the contact time. Maximum carbofuran removal was observed at pH 2.0. The physical and chemical characterization was carried out, FTIR spectra indicated the presence of bonded OH-, -CH2 and —CH3, C=O, C=C, NH, asymmetric and symmetric C-O-H, C-O-C and glycosidic Cl-H deforming with ring vibration on the NazCCL modified adsorbent. The elemental analysis illustrated that the content of C, O, H, N and S was 48.77%, 42.89%, 7.32%, 1.99%, and 0.03% respectively, while proximate analysis revealed that the ash, volatile and moisture content was 7.56%, 86.53% and 5.91%. Among the tested isotherm model, Langmuir model provided the better correlation, R2 and RMSD of 0.998 and 0.639, respectively, with a maximum monolayer adsorption capacity of 149.15 mg/g at the operating temperature of 30°C. The calculated AG° was -2.322 J/mol, -0.893 J/mol, and 0.377 J/mol; AH° and AS° were -42.23 J/mol and -135.10 J/mol, respectively. The negative value of AH° indicated the exothermic nature of the adsorption interaction. These results can be helpful in designing a batch mode system for the removal of carbofuran from dilute wastewater. The findings revealed the potential of modified corn cob as a low economical and eco-friendly biosorbent as compared to the commercial adsorbents.